Technological and social dimension on acceptance of social networking sites among students in higher learning institutions - Yahya, Yazriwati (2022)
One of the purposes students in higher learning institutions use social networking sites (SNS) is to communicate with one another. This purpose is significant, especially during the Covid-19 pandemic, which recently spread worldwide. Most research on SNS acceptance in higher education used the same Information System (IS) theories (such as Technological Acceptance Model), focusing more on the technological side. Thus, there is a lack of research on students‟ SNS acceptance, focusing on the technological and social dimensions using other IS theories. This study aims to identify the technological and social factors affecting SNS acceptance among students in Malaysia‟s higher learning institutions. A conceptual model was developed based on the identified potential factors and the underpinning theory of Unified Theory of Acceptance and Use of Technology 2 (UTAUT2). The UTAUT2 was chosen to fill in the research gap because it was related to the use of other IS theories in SNS acceptance studies. The data collection was conducted at various Malaysia Higher Learning Institutions using the survey form, and 498 responses were recorded. The data were analysed using SPSS 26.0 for descriptive analysis of demographic data and Partial Least Square-Structured Equation Modelling for validating the conceptual model. The model validation revealed that Effort Expectancy, Habit, Hedonic Motivation, Privacy Concern, Social Value, and Trust affected SNS Behavioral Intention significantly. Whereas Facilitating Conditions, Habit, Social Value, Technology Cluster, and Behavioral Intention had significant effects on SNS Use Behavior. The R² value of endogenous constructs in this study is 0.558 for SNS Use Behavior. The identified factors in this study explained that 55 % of the variance accepted the use behaviour of SNS among the students, showing a good explanatory power of the model. In addition, SNS Behavioral Intention also acted as a mediator between Effort Expectancy, Hedonic Motivation, Trust, Privacy Concern and Habit with SNS Use Behavior. Apart from that, the moderator effect analysis showed that gender, education level and personality traits acted as positive moderators between the factors and SNS Behavioral Intention and SNS Use Behavior. This research contributed to the theoretical knowledge of SNS technology acceptance in the context of technological and social context measurements. In addition, the research outcome will benefit the Malaysia Ministry of Higher Education, the higher education student administrator, lecturers and the SNS service providers. The research outcome will contribute to the development of creating an atmosphere of new and innovative ways to communicate fast and easily with the students. This will nurture students‟ moral beliefs and principles that are accepted by society.